Peran Orang Tua dalam Mendidik Anak Sejak Dini di Lingkungan Keluarga - Erzad, Azizah Maulina (PIAUD Universitas Islam Negeri Sunan Kudus, 2017)
Abstract: THE PARENTS' ROLE IN EDUCATING CHILDREN SINCEINFANCY IN THE FAMILY. The child is a boon and mandate entrusted byGod to His servant who will be asked for the responsibility in the Hereafter.The obligation as a parent is to provide education to children starting froman early age. The development of early childhood is strongly bound by theenvironment and the family. This paper aims to describe the role of parentsto the education of children. The study in this paper uses literature study orlibrary research method. The result of this study is that family is the firstplace where children get education. Children's character and personality isformed first in the family. Parents should have a concept or provision ineducating their children that includes moral or character education,science education, religious education, be fair to the children, and giveattention and affection to children. Parents become role models for theirchildren. Therefore, the role of parents is very important in thedevelopment and formation of children's character from an early age.Anak merupakan anugerah dan sekaligus amanah yangdititipkan oleh Allah kepada hambaNya yang akan dimintaipertanggungjawabannya di akhirat kelak. Kewajiban sebagai orang tuaadalah memberikan pendidikan kepada anak yang dimulai sejak usiadini. Perkembangan pada anak usia dini sangat terikat oleh lingkungandan keluarganya. Tulisan ini bertujuan untuk menjabarkan peran orangtua terhadap pendidikan anak. Kajian dalam tulisan ini menggunakanmetode studi kepustakaan (library research). Hasil dari kajian ini yaitubahwa keluarga merupakan tempat pertama dimana anak memperolehpendidikan. Karakter dan kepribadian anak dibentuk pertama kali didalam keluarga. Orang tua hendaknya memiliki konsep atau ketentuandalam mendidik anaknya yang meliputi pendidikan moral atau karakter,pendidikan ilmu pengetahuan, pendidikan ilmu agama, bersikap adilterhadap anak, serta memberikan perhatian dan kasih sayang kepadaanak. Orang tua menjadi suri tauladan bagi anak-anaknya. Oleh sebab ituperan orang tua sangatlah penting dalam perkembangan danpembentukan karakter anak sejak dini.